¿QUIÉN CUIDA A QUIÉN? APORTES DE LAS PERSONAS ADULTAS MAYORES - López Ruiz, Luis Ángel (Universidad de Costa Rica, 2021)
The purpose of this study is to analyze the time invested by the elderly Costa Rican population in care work. This research can be considered of an exploratory nature, given the lack of research on this topic in our context. The methodology used is quantitative, based on data compiled from a Time Use Survey (enut-2017, in Spanish). A factor analysis model was used to construct the indicators. The results confirm that elderly people invest a large part of their time into care work, hence it cannot be affirmed that they spend less time on care work than younger people.